Designing database applications with objects and rules : - Ceri, Stefano (Addison-Wesley, 1997)
This book takes the reader through the various stages of the Methodology, introducing the models and languages used, explaining the structured development process from analysis through to implementation and finally explaining how to put the Methodology to work.